Development of Smart Safety Net at Level Crossings for Indian Railways - Dr. Amit Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Each Level Crossing (LC) has unique and typical characteristics. These high-risk intersection spots of transport system in general and railways in particular are matter of concern all over the world. The operation of trains is under the control of railways and at the same time road transport may be under the control of various other transport agencies. There may be uniform road design standards and traffic operation bye-laws in a country but the movement of traffic and pedestrians are seldom planned, monitored and regulated. This freedom and uncontrolled movement of road users make these intersections more vulnerable to accidents. Each year a large number of accidents take place at LCs throughout the world. The majority of these accidents occur due to the negligence, and incompetence of road users, who generally operate their vehicles in the environment where ignorance of safety rules and safety measures are in practice. Human factors have been ignored till sometimes back while considering safety at railway crossings. Consequently, most of the protection systems and alarming systems employed at railway LC relied upon technology and traditions only. A smart, dynamic integrated system of safety net, particularly suitable for Indian Railways has been developed to take care of various safety aspects at rail-road level crossing. The system is based on modern technology and behavioral psychology of the road users. The system consists of digital sensors, microcontroller (AT mega 328P), buzzer, signal lights, flippers, comparator and position encoder. It is an automatic and supposedly, fool proof system for safe operations at level crossings.